Pitch and vowel space characteristics of maternal speech to children with and without hearing loss - Jyothi Shivaswamy; Animesh Barman; Santosh Maruthy (The Egyptian Journal of Otolaryngology)
Abstract Background Children with hearing loss face unique challenges in acquiring speech and language, as hearing impairment significantly influences their natural interactions with caregivers. Understanding the characteristics of speech input that children with hearing loss typically experience, as compared to normal-hearing children and adults, is crucial for developing effective interventions and support strategies. The study aims to compare the pitch characteristics, vowel space area, and dispersion between speech directed by mothers of children with hearing loss and normal-hearing children. Methods The speech of native Kannada-speaking mothers directed to their children with hearing loss was compared individually with the speech directed to their normal-hearing children. Additionally, the speech directed to both groups of children—those with hearing loss and those with normal hearing—was separately compared with the speech directed to adults. Pitch characteristics and vowel space of mother’s speech were analyzed using Praat. Results The study demonstrated a larger vowel space area and dispersion in the mother’s speech directed to children with hearing loss compared to children with normal hearing and adults. Across children of different ages and hearing statuses, fundamental frequency (F0), minimum F0, and maximum F0 were consistently higher in speech directed towards both groups of children. Conclusion The findings suggest that mothers adapt the prosodic features of their speech based more on their child’s hearing experience than on their age. Children with hearing impairment may require more effort from mothers to maintain engagement during interactions compared to those with normal hearing.